VALIDATION OF ANTIBODY RAPID TEST FOR SEVERE ACUTE RESPIRATORY SYNDROME CORONAVIRUS-2 INFECTION IN BETHESDA HOSPITAL YOGYAKARTA - Fenty Fenty; Ivan Lim; Frida E. W.; Kristiani D.; Rizaldi Pinzon (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2021)
Since March 2020, Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) infection has been around in Indonesia with a case fatality rate was 4.7% on August, 1th 2020. So far, the Real-Time Polymerase Chain Reaction (RT-PCR) method is the gold standard for the SARS-CoV-2 infection diagnosis. This method, however, has some limitations where it has a longturnaround time, complicated operations, and high prices. Hence, the rapid test kits are now readily available to identify the SARS-CoV-2 patients. The purpose of this study is to measure the diagnostic performance, including sensitivity, specificity, positive and negative predictive value, likelihood ratio or LR of antibody rapid test if compared with RT-PCR for the SARS-CoV-2 suspected patients in Bethesda Hospital Yogyakarta. This research was analytical observational research with a cross-sectional design approach, in which data were collected retrospectively. The instruments used in this study included e-medical record (ERM), Laboratory Information System (LIS) data from patients with suspected SARS-CoV-2 infection in Bethesda Hospital Yogyakarta. We collected demographic data of patients, RT-PCR results, antibody rapid test results using Standard Q COVID-19 IgM/IgG Combo. The data were obtained from 50 patients. The results showed that the Rapid test kit has a 100% sensitivity value, 74.4% specificity value, 38.9% positive and 100% negative predictive value, 3906 positive likelihood ratio compared with the RT-PCR results.